DR. REFIK SAYDAM (1882-1942) THE FIRST MINISTER OF HEALTH OF THE REPUBLIC OF TURKIYE - Ada, Turhan (NOBEL ILAC, 2024)
Born in Istanbul in 1882, Dr. Ibrahim Refik Saydam graduated from the Military Medical School in 1905 with the rank of Captain. Following his successful performance in the Balkan Wars, with the beginning of World War I, he was appointed as Deputy General Inspector of General Headquarters Sahra Sanitary and continued his duty until the signing of the Armistice of Mudros. IX. He actively participated in the War of Independence process as a member of the delegation that went to Samsun with Mustafa Kemal Pasha in the capacity of Army Inspector, Deputy Chief of Sanitary Affairs and served as Deputy of Sanitary and Civil Aid between 10 March 1921 and 20 December 1921. Dr. was appointed to the same position again during the Republic period. Dr. Saydam continued his duty from March 4, 1925 to October 25, 1937, and organized successful organizations that maintain their impact today in the establishment of health infrastructure and the fight against infectious diseases. He passed away on July 8, 1942, while he was on duty.
Keywords: Refik Saydam; national struggle; Turkish Grand National Assembly; prime ministers; General & Internal Medicine